The Abuses of Punishment - Adams, R. author. aut Link
X, 270 p.
Keywords: This book argues that abusive punishments are particularly deeply rooted in authoritarian states and in some Western countries such as Britain and the USA, from which they have been exported over past centuries. The book surveys a variety of psychological, physically constraining, custodial, corporal and capital punishments. The implicit punitive content of judicial processes such as trial, as well as treatments such as behavioural therapy, may have as much psychological impact as more explicitly physical punishments.